A complex role of anthrax toxin receptor 2 polymorphisms and capillary morphogenesis protein 2 in ankylosing spondylitis pathogenesis. Issue 9 (September 2016) - Zhang, Zhijian; Yu, Kun; Dai, Dongfa; Yuan, Fang; Liang, Fei; Liu, Nan; Xi, Yongzhi; Sun, Yu-Ying
Abstract This study investigated the role of anthrax toxin receptor 2 (ANTXR2) gene polymorphisms and capillary morphogenesis protein 2 (CMG2) expression in susceptibility and pathogenesis to ankylosing spondylitis (AS) in the Han Chinese in Beijing. A case-control study was performed using 602 AS patient samples meeting the revised New York criterion and 619 matched controls from Han Chinese individuals. Nineteen single-nucleotide polymorphisms (SNPs) of ANTXR2 genes were selected and genotyped using the Sequenom iPlex platform. Real-time polymerase chain reaction and flow cytometry were performed to investigate the impact of SNP polymorphisms on ANTXR2 transcription and CMG2 expression, respectively. The association of variants with AS was examined with UNPHASED 3.1.5. A novel association was observed between AS and three SNPs in the ANTXR2 gene (rs4690127, rs6823031, and rs4333130;P  = 0.004, 0.011, and 0.013, respectively), confirming the association between rs433130 and AS in the Han Chinese. The strongest haplotype association was observed with rs4690127-rs6823031-rs4333130 (P  = 2.5 × 10−4 ). rs6534639 and rs4333130 showed a cis-interaction (P  = 0.027) in AS. ANTXR2 messenger RNA (mRNA) expression was significantly higher in the AS group than in the control group (P  = 0.039). CMG2 expression in the lipopolysaccharide (LPS)-stimulated group was significantly lower than that in the control group (P  = 0.018). This study reports a novel association between ANTXR2 and AS in the Han Chinese. ANTXR2 genetic polymorphisms affect ANTXR2 mRNA transcription and CMG2 expression. The opposing results observed for ANTXR2 transcription and CMG2 expression suggest a complex role of ANTXR2 polymorphisms in AS pathogenesis.